Energy Transfer between AGuIX Nanoparticles and Photofrin under Light or X-ray Excitation for PDT Applications - Batoul Dhaini; Philippe Arnoux; Joël Daouk; François Lux; Olivier Tillement; Agnès Hagège; Tayssir Hamieh; Gal Shafirstein; Céline Frochot (MDPI AG, 2024)
Photodynamic therapy is an accepted therapy cancer treatment. Its advantages encourage researchers to delve deeper. The use of nanoparticles in PDT has several advantages including the passive targeting of cancer cells. The aim of this article is to evaluate the effectiveness of AGuIX nanoparticles (activation and guiding of irradiation by X-ray) in the presence or absence of a photosensitizer, Photofrin, under illumination of 630 nm or under X-ray irradiation. The goal is to improve local tumor control by combining PDT with low-dose-X-ray-activated NPs in the treatment of locally advanced metastatic lung cancer. The study of the energy transfer, which occurs after excitation of Gd/Tb chelated in AGuIX in the presence of Photofrin, was carried out. We could observe the formation of singlet oxygen after the light or X-ray excitation of Gd and Tb that was not observed for AGuIX or Photofrin alone, proving that it is possible to realize energy transfer between both compounds.